2016
DOI: 10.1128/jvi.01469-16
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Strategies Reveal a Bidentate Interaction between the Nipah Virus Attachment and Fusion Glycoproteins

Abstract: The paramyxoviral family contains many medically important viruses, including measles virus, mumps virus, parainfluenza viruses, respiratory syncytial virus, human metapneumovirus, and the deadly zoonotic henipaviruses Hendra and Nipah virus (NiV). To both enter host cells and spread from cell to cell within infected hosts, the vast majority of paramyxoviruses utilize two viral envelope glycoproteins: the attachment glycoprotein (G, H, or hemagglutinin-neuraminidase [HN]) and the fusion glycoprotein (F). Bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…To investigate the organization of the viral envelope glycoproteins on the plasma membrane, we used FLAG-tagged F 21 and hemagglutinin (HA)-tagged G 22 constructs (Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the organization of the viral envelope glycoproteins on the plasma membrane, we used FLAG-tagged F 21 and hemagglutinin (HA)-tagged G 22 constructs (Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…3H ). 23 One typical previous example of the bidentate effect is that deubiquitinase hOtu1 specifically recognizes K48 diUb through binding to both the proximal and the distal Ub of K48 diUb at different binding sites simultaneously. 24 …”
Section: Resultsmentioning
confidence: 99%
“…Instead, a bidentate interaction exists between NiV-F and both the globular head and 4HB stalk of NiV-RBP ( Figure 7B, Panel 1). Indeed, flow cytometric strategies with various truncated versions of soluble NiV-G and full length NiV-F expressed on cells confirmed this bidentate interaction [151]. This study also showed the soluble ectodomain version of NiV-G is not sufficient to induce cell-cell fusion, and only membrane-bound NiV-G triggers F. The data suggests anchoring of NiV-G is necessary for F activation or the transmembrane domain and/or cytoplasmic tail of G is involved in the fusion process.…”
Section: Characteristics Of Rbp-g For Triggering: a Unique Proline-rimentioning
confidence: 80%
“…Interaction is bidendate, involves head and stalk [151]; in the context of full length NiV-G, both head and stalk are necessary for productive NiV-F triggering [152] Interaction and triggering occur through the stalk domain [104,[147][148][149] The C-term of the stalk can be elongated by 41-residues, adding a pitch of~75 Å above residue 118, and triggering will still occur [108]; results suggest that interaction between…”
Section: Characteristics Of F/rbp Interaction In Triggering Fmentioning
confidence: 99%